Durabilitas Campuran AC-BC yang Menggunakan Batu Gunung Baba Kabupaten Tana Toraja - Cindy Pasilaputri; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2021)
Several factors that can affect road damage are excessive traffic load, temperature (weather), water, and pavement construction that does not meet the technical requirements. The durability of an asphalt mixture is the resistance of the mixture to the effects of water, water vapor, and temperature. A mixture with a high durability value provides a good mix quality and long-term use. The purpose of this study was to determine the durability of the AC-BC mixture using Mount Baba stone. The general specifications of Bina Marga in 2018 are the reference in this study. By using the standard Marshall test method, the results obtained through the Marshall AC-BC mixture immersion test with a duration of immersion time of 0.5 hours, 12 hours, 24 hours, 36 hours, 48 hours, 60 hours with a durability value of 95.49% - 86.99%. The increase in immersion time causes a decrease in the durability of the mixture.